The archival knowledge organization: the rise of a Brazilian discursive community - da Silva, Amanda Marissa Soares; Tognoli, Natália [UNESP] (My University, 2022)
The article analyzes the rise of a Brazilian discursive community as a research elite in the archival knowledge organization. It discusses the relationship between archival science and knowledge organization from the analysis of archival themes within the International Society for Knowledge Organization proceedings, recognizing the seminal role of the Brazilian discursive community to the setting and rec-ognition of archival science studies as part of knowledge organization.
La organización del conocimiento archivístico: el surgimiento de una comunidad discursiva brasileña
A organização do conhecimento arquivístico A emergência de uma comunidade discursiva brasileira
Keywords: archival knowledge organization; discursive com-munities; International Society for Knowledge Organization